Analisis Pengaruh Rasio BOPO, CAR dan NPL Terhadap Kinerja Keuangan Pada PT Bank Central Asia Tbk. - FH, Nur Fadilah; Muniarty, Puji (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This research was conducted at PT Bank Central Asia Tbk. With the aim of knowing and analyzing the health of banks with BOPO, CAR and NPL ratios and looking for their influence on financial performance (ROA). The research method used is associative quantitative research. The sample for this study consisted of balance sheets, income statements and notes to financial statements (CALK) for 15 years from the period 2007 - 2021 with the sampling technique used being purposive sampling. The analytical tools used are classical assumptions, multiple linear regression, Coefficient of Determination, Multiple Correlation, Partial t-test, and Simultaneous f-test which aims to analyze the relationship between BOPO, CAR and NPL variables on financial performance (ROA) using SPSS v software. 16. The results of this study indicate that BOPO has a significant effect on ROA, for CAR and NPL it does not have a significant effect on ROA. Meanwhile BOPO, CAR and NPL together have a significant effect on ROA.